The Development of automatic melinjo puncher machine using pneumatics pressure - Hendriko Hendriko; Alfiandis Lafebri; Made Rahmawaty; Tianur Tianur (Universitas Negeri Padang, 2021)
Melinjo chip is one of Indonesia’s facourite food. Melinjo chip is not only marketed in Indonesia, but they have been exported to various countries including Netherlands, United State of America, and Middle East. Mostly melinjo chips are produced in the traditional way by home industry and MSMEs. The existing machines to produce melinjo chips are not operated fully automatically; hence they still require significant operator involvement. The machine developed in this study uses a pneumatics pressure as power driver. Pneumatics cylinders are used to push the melinjo seeds onto the flattening base, and to move the puncher rod during flattening process. The developed automatic melinjo punching machine has been tested. The tests were carried out to determine the parameters used for programming the machine, sucah as punching time and pneumatic presure, and for checking the capacity of the machine. The test results show that the most effective punching time is 5 seconds at pressure between 5-7 bar. In 5 seconds, the machine can change melinjo seed into chips shape with thickness in between 1,20-1,45 mm. The capacity of the machine in processing melinjo has also been tested. The results showed that this machine can process 528 melinjo into chips shape melinjo per hour.